Pengaruh Faktor Budaya Organisasi Terhadap Peningkatan Kinerja Anggota KPU Kabupaten Dairi - Sidauruk, Martua Batako; Umboro, Kristiant Haryo; Muthmainnah; Marbun, Wilson Saripati Raja; Nasti, Nilawati; Helmi, Tengku Ahmad (Jurnal EMT KITA, 2024)
This research aims to identify and analyze the influence of organizational culture factors on improving the performance of members of the Dairi Regency General Election Commission (KPU). This research method uses a quantitative approach by distributing questionnaires to members of the Dairi Regency KPU as respondents. The research results show that organizational culture factors, such as shared values, norms, and symbols contained in the KPU work environment, have a significant positive influence on the performance of KPU members. The organization's success in creating an inclusive, transparent, and public service-oriented culture plays a key role in increasing the effectiveness and efficiency of the general election process in Dairi Regency. Understanding and implementing organizational values, such as integrity, professionalism, and active participation in the decision-making process, forms the basis of a positive organizational culture. Norms that support teamwork, fairness, and accountability also make a significant contribution to the performance of KPU members. This research provides recommendations to the Dairi Regency KPU to strengthen and maintain a positive organizational culture. Increasing understanding of shared values, increasing member participation, and implementing norms that support effective and transparent work are expected to improve the KPU's performance and the quality of general elections in the region. The implications of this research can also be applied to similar institutions to strengthen aspects of organizational culture to achieve better organizational goals